Drug-tolerant persister cell in cancer: reversibility, microenvironmental interplay, and therapeutic strategies - Li, Haifeng; Xu, Wenlong; Cheng, Wenqi; Yu, Guanxiao; Tang, Dongmei (Frontiers in Pharmacology, 2025)
Drug-tolerant persister (DTP) cells are a subpopulation of cancer cells capable of surviving therapeutic stress through reversible, non-genetic adaptations. These cells contribute to minimal residual disease and eventual tumor relapse. Understanding the mechanisms that govern the entry into and exit from the DTP state—such as epigenetic remodeling, metabolic rewiring, and transcriptional plasticity—reveals actionable vulnerabilities. This article reviews the biological basis of DTP reversibility, outlines the major challenges in targeting these cells, and proposes innovative therapeutic strategies including epigenetic inhibitors, metabolic disruptors, and adaptive dosing regimens. We also highlight the importance of biomarker development and dynamic monitoring. Targeting DTP cells at their reversible stage may prevent permanent resistance, offering a promising avenue to improve treatment durability and patient outcomes in cancer therapy.